1985
DOI: 10.1002/1097-4679(198505)41:3<359::aid-jclp2270410308>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Life skill Training: Psychoeducational training as mental health treatment

Abstract: Fifty‐four patients of a Veterans Administration Medical Center were assigned to either a life‐skill training program that emphasized psycho educational instruction and skill building or to a group counseling control condition. Subjects assigned to life‐skill training were provided with 28 hours of instruction in interpersonal communication, purpose in life problem solving, and physical fitness/health maintenance. Control subjects received equal time engaged in psychiatric treatment that emphasized the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In accordance with the literature on skills training for psychiatric patients, Life Skills is perceived as most beneficial in the interpersonal realm, increasing individuals' social functioning in a variety of situations (Bedell et al, 1997;Benton & Schroeder, 1990;Dilk & Bond, 1996;May et al, 1985;Pratt & Mueser, 2002). Not surprisingly, many participants indicated that the poor attendance of other students, the videotaping of exercises, and discomfort with role-playing exercises were problematic aspects of their Life Skills experiences.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In accordance with the literature on skills training for psychiatric patients, Life Skills is perceived as most beneficial in the interpersonal realm, increasing individuals' social functioning in a variety of situations (Bedell et al, 1997;Benton & Schroeder, 1990;Dilk & Bond, 1996;May et al, 1985;Pratt & Mueser, 2002). Not surprisingly, many participants indicated that the poor attendance of other students, the videotaping of exercises, and discomfort with role-playing exercises were problematic aspects of their Life Skills experiences.…”
Section: Discussionmentioning
confidence: 55%
“…The stress-vulnerability model conceptualizes mental illness as a product of a biological susceptibility that manifests itself, or is exacerbated, in the presence of stress. Life Skills coaches teach students how to adaptively cope with stressful life events; this training decreases the severity of psychiatric symptoms and=or minimizes the likelihood of relapse by increasing the participant's level of psychosocial functioning (Ford & Urban, 1998;Gazda, 1982;May, Gazda, Powell, & Hauser, 1985;Pratt & Mueser, 2002;Segrin & Givertz, 2003). Social skills training has been described as the ''single most important innovation for the psychological treatment of persons with serious mental illness'' (Bedell, Hunter, & Corrigan, 1997, p. 220).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with bipolar disorder (BD) display memory impairments even in remission . Intact memory functions are essential to maintain adequate community living skills , defined as a combination of practical skills necessary to live independently outside the hospital . The aforementioned studies refer to retrospective memory (RM), that is, the ability to recall past events .…”
mentioning
confidence: 99%
“…Past research supports life skills traininig efficacy among a wide variety of groups including penitentiary inmates (Marshall, Turner, & Barbaree, 1989;Reker & Meissner, 1977); veteran psychiatric patients (May, Gazda, Powell, & Hauser, 1985;Powell & Clayton, 1980;Powell, Illovsky, O'Leary, & Gazda, 1988); the mentally retarded, learning disabled, and emotionally disturbed (Gresham, 1981); young adults with chronic mental disorders (Lehman et al, 1986); short-term psychiatric inpatients (Griffin-Shelley & Trachtenberg, 1985); long-term psychiatric inpatients (Griffin-Shelley & Wendel, 1988); psychiatric outpatients (Falloon, Lindley, McDonald, & Marks, 1977); individuals who display avoidant personality disorder (Stravynski, Lesage, Marcouiller, & Elie, 1989); and chronic schizophrenics (Brown & Munford, 1983). Although the improvement of psychosocial adjustment is a major aim of life skills training (Gazda & Powell, 1981), few studies have examined the degree to which psychosocial adjustment may change as a result of participation in such a program.…”
mentioning
confidence: 99%